The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.3766/jaaa.22.7.2
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Processing in Low-Frequency Channels: Effects of Age and Hearing Loss in Middle-Aged Listeners

Abstract: The conclusions from the present study are twofold: (1) HFSNHL may have an off-channel impact on auditory temporal processing, and (2) presenescent changes in the auditory system of MANH subjects increased self-perceived problems hearing in background noise and decreased functional performance in background noise compared with YNH subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 44 publications
(67 reference statements)
2
18
0
Order By: Relevance
“…In a recent study involving young (< 30 years) and older (≥ 60 years) participants with normal individual and matched mean audiograms, Füllgrabe, Moore, and Stone (2012) showed that TFS sensitivity was reduced in the older participants and was indeed associated with the ability to identify speech in noise, but not without the amount of masking release. It will be of interest to establish whether the early midlife reduction in TFS sensitivity observed here coincides with difficulties in speech identification, as suggested in subjective reports (Leigh-Pfaffenroth & Elangovan, 2011).…”
Section: Resultsmentioning
confidence: 65%
“…In a recent study involving young (< 30 years) and older (≥ 60 years) participants with normal individual and matched mean audiograms, Füllgrabe, Moore, and Stone (2012) showed that TFS sensitivity was reduced in the older participants and was indeed associated with the ability to identify speech in noise, but not without the amount of masking release. It will be of interest to establish whether the early midlife reduction in TFS sensitivity observed here coincides with difficulties in speech identification, as suggested in subjective reports (Leigh-Pfaffenroth & Elangovan, 2011).…”
Section: Resultsmentioning
confidence: 65%
“…Specifically, we reasoned that reverberation might expose effects of early aging, which could help explain why middle-aged listeners report difficulties in challenging listening conditions [2, 15, 16]. In an initial study with young adult to middle-aged normal-hearing listeners (designed to emphasize sensory effects and minimize cognitive factors), we found that reverberant energy interferes with the ability to selectively attend to a speech stream amid similar competing streams [4].…”
Section: Resultsmentioning
confidence: 99%
“…Children with listening difficulties are often diagnosed with auditory processing disorder, but their listening difficulty might actually result from poor attention rather than from impaired sensory processing [5], [47]. Similarly, the aged population often complains of listening difficulties despite normal audiometric scores [48], [49]. An independent test of auditory attention like the TAIL would help to identify how much those difficulties arise from a declining cognitive control system.…”
Section: Discussionmentioning
confidence: 99%